Brassica juncea nitric oxide synthase like activity is stimulated by PKC activators and calcium suggesting modulation by PKC-like kinase - Talwar, Pooja Saigal (Plant physiology and biochemistry : PPB, 2012)
Copyright © 2012 Elsevier Masson SAS. All rights reserved.